2014
DOI: 10.1007/s11095-014-1518-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultra-High Pressure Homogenization on the Interaction Between Bovine Casein Micelles and Ritonavir

Abstract: Purpose The aim of this work was to develop a milk-based powder formulation appropriate for pediatric delivery of ritonavir (RIT). Methods Ultra-high pressure homogenization (UHPH) at 0.1, 300 and 500 MPa was used to process a dispersion of pasteurized skim milk (SM) and ritonavir. Loading efficiency was determined by RP-HPLC-UV; characterization of RIT:SM systems was carried out by apparent average hydrodynamic diameter and rheological measurements as well as different analytical techniques including Trp fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A separate study evaluated the effectiveness of a milk-based powder formulation of ritonavir to ease administration to infants and children. It found that casein micelles, a milk protein, are an efficient carrier system of ritonavir and serve to decrease bitter taste [ 68 ].…”
Section: Benefits Of Child-friendly Artmentioning
confidence: 99%
“…A separate study evaluated the effectiveness of a milk-based powder formulation of ritonavir to ease administration to infants and children. It found that casein micelles, a milk protein, are an efficient carrier system of ritonavir and serve to decrease bitter taste [ 68 ].…”
Section: Benefits Of Child-friendly Artmentioning
confidence: 99%
“…Environmental factors, including pH, solvent, and pressure, were explored extensively to dissociate and reassemble casein micelles to bind and deliver various hydrophobic (poorly water-soluble) nutraceuticals. These modified casein micelles were used to nonspecifically bind vitamin D 2 , curcumin, and ritonavir, among others (Semo et al, 2007;Pan et al, 2014;Corzo-Martínez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that UHPH treatment of skim milk at 186 MPa subjects casein micelles to such extreme cavitation, turbulence, and shear forces that the hydrophobic and ionic interactions responsible for stabilizing the casein micelle structure are disturbed, drastically reducing their size and/or causing them to disintegrate [ 26 ]. When casein micelles, formed by β- - - and κ-caseins (molar ratio 4:1:4:1.3), are disintegrated at certain UHPH pressures, a release of calcium, phosphate, and amino acids as well as an increase in viscosity of skim milk may be observed due to the aggregation of smaller structures such as neo-micelles and β-lactoglobulin molecules and higher protein–protein interactions, especially at pressures higher than 300 MPa [ 35 , 36 ]. This may explain why the current data suggested that UHPH processing at 150 MPa increases the protective properties of skim milk when used as microencapsulating agent for LP but this protective effect is greatly reduced or eliminated when the skim milk has been processed at pressure higher than 150 MPa- excessive micelle aggregation may limit the ability of those micelles to interact with the probiotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…A high degree of disruption of hydrophobic and ionic interactions that results in a partial or total disintegration of the casein micelles produced by the cavitation, turbulence, and shear forces are observed at high pressures [ 26 ]. However, excessive UHPH pressures can induce the coalescence of casein micelles, increase the aggregation of smaller structures, such as neo-micelles and β-lactoglobulin molecules, and boost the protein–protein interactions, which increases the viscosity of skim milk substantially (especially at pressures higher than 300 MPa) [ 32 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%